106P A single dose of local IL-12 promotes anti-tumor effect of anti-EGFRvIII-CAR-T cells in a syngeneic murine model of glioblastoma. (15th December 2019) - Liuzzi, A R; Agliardi, G; Becher, B; Pule, M
Abstract: Background: Glioblastoma multiforme (GBM) is one of the most devastating brain tumors with poor prognosis and high mortality. Immunotherapy with chimeric antigen receptor (CAR) T cells is gaining attention as a promising strategy to treat this disease. An ideal candidate to target with CAR T cells is the tumor specific variant III of the epidermal growth factor receptor (EGFRvIII), which represents a mutation found in more than 30% of glioblastoma patients. However, anti-EGFRvIII-CAR modified T cell therapy has shown only limited effects in GBM patients, in all likelihood due to the immunosuppressive microenvironment that CAR T cells encounter in the tumor microenvironment (TME) of gliomas. To make gliomas susceptible to CAR T cell therapy, combinatorial approaches to convert the TME are required. Methods: Mice received 5Gy TBI on day 15 post implantation, followed by intra-tumoral injection of IL-12:Fc on day 20 and infusion of EGFRvIII-directed CAR or non-transduced T cells on day 21. To perform functional analysis, we adopted high-parametric flow-cytometric characterization of the TME using 23 independent parameters 8 days after CAR T cells injection. We utilized unsupervised validated clustering approaches (FlowSOM and CellCNN) to discriminate between different cell populations. Results: Here, we demonstrate that the combination of a single dose of local IL-12 with anti-EGFRvIII-CAR T cells synergizes to increase long-term survival in a syngeneic mouse model of GBM. IL-12 not only boosted the pro-inflammatory and cytotoxic activity of anti-EGFRvIII-CAR T cells, but also induced a complete remodelling of the tumor microenvironment (TME) with strong endogenous anti-tumor immune T cell responses. These findings highlight the capacity of IL-12 to induce an immunologically "cold" tumor such as GMB to acquire responsiveness to CAR T cells therapy. Conclusion: This study demonstrates the capacity of IL-12 as local "adjuvant" therapy to boost the efficacy of CAR T cells and to awake the endogenous anti-tumor T cell responses. Legal entity responsible for the study: University of Zurich. Funding: University Research Priority Project and Advanced T-cell Engineered for Cancer Therapy. Disclosure: M. Pule: Honoraria (self), Honoraria (institution): Autolus LTD. All other authors have declared no conflicts of interest.